Managing projects : (Harvard Business Review Press, 2014)
You've been asked to manage a key project–or perhaps you've volunteered for an assignment that could advance your career. SO how do you make sure the project succeeds? Managing Projects walks you quickly through the basics, including: drawing up a realistic schedule and project plan; monitoring key tasks and benchmarks; communicating with stakeholders; bringing the project to a close.